G protein–coupled receptor kinase 2 at crossroads of metabolic and cardiovascular diseases. (February 2021) - Arcones, Alba C.; Murga, Cristina; Penela, Petronila; Inserte, Javier; Mayor, Federico
Abstract: G protein–coupled receptor kinase 2 (GRK2) is the center of a signaling hub shared by G protein–coupled receptors and insulin networks controlling heart function and metabolism as well as global energy homeostasis. GRK2 levels and activity are upregulated in the heart and in tissues that are the key to metabolic control during cardiovascular pathologies and in obesity and insulin resistance–related contexts, which are frequent comorbidities in the clinical practice, pointing to this protein as a potentially relevant therapeutic target. Recent research is unveiling the signals and mechanisms involved in the modulation of GRK2 expression and functionality in these physiopathological contexts and disclosing how altered GRK2 levels contribute to disease progression by modulating the functionality and cross talk of cardiac and metabolically relevant tissues. Highlights: Cardiac G protein–coupled receptor kinase 2 (GRK2) levels are dynamically regulated by a variety of pathological stimuli. GRK2 is altered in interconnected tissues in cardiovascular and obesity-related diseases. GRK2 integrates key signaling networks in the heart and metabolically relevant tissues. GRK2 levels in given cell types affect metabolic homeostasis via organ cross talk. GRK2 modulation emerges as a therapeutic strategy for cardiometabolic diseases.